Reducing the effects of bullying in adolescence: the roles of schools and families. - Burk Cahoj, Joan (Kansas State University, 2011)
The increasing incidence of school-related bullying problems has caught the attention of the media in the United States and rest of the world. The bullying phenomenon has administrators, educators, school site councils, and parents searching for effective prevention programs to reduce youth peer violence and improve the learning environment for students. Many schools are required by state laws to have bullying intervention and prevention programs in place; however, questions arise about the success of popular and widely-used bullying prevention programs. Research data shows that zero-tolerance policies, which appeal to those who demand a strong disciplined reaction to peer violence, are often implemented without using common sense. Many parents or guardians of victimized children are either unaware of the problem, or they do not know what to do when their children are bullied. This report reviews current knowledge about bullying in school during adolescence. It begins by looking at the historical context of bullying and bullying research, and then examines adolescent development in relationship to bullying behaviors. The literature review includes topics regarding types and definitions of bullying, bully, victim, and bully-victim profiles, and well as the role of the bystander. Using Bronfenbrenner’s bio-ecological model of human development, this report then identifies the need for parental involvement as a way to help adolescents cope with bullying incidents.
Keywords: Bullying; Adolescence; Families; Schools; Olweus; Family life education; Individual & Family Studies (0628)